Impact of Acute Complications on The Course and Outcome of Severe COVID-19: a Clinical Analysis and Determination of Mortality Predictors - Tetiana D. Danilevych; Lesia V. Rasputina (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To establish the features of the clinical picture, the structure of acute complications and predictors of mortality in patients with a severe course of COVID-19.Materials and methods. 221 patients who were in the intensive care unit (ICU) of City Clinical Hospital No. 1 in Vinnytsia, Ukraine were examined in the period 2020-2023. Among them, 133 (60.2%) patients survived and 88 (39.8%) of patients died as a result of a severe course of COVID-19 (p = 0.02).Results. The mortality rate of patients with a severe course of COVID-19 was 39.8%. Among patients classified as categories 6 and 7 by the WHO, the highest mortality was observed, (p<0.001). In the group of deceased patients, there were significantly more patients with hypertension (73 (83.0%) vs. 90 (67.7%), p=0.008), coronary heart disease (CHD) (83 (94.3%) vs. 91 (68.4%)), p = 0.0001), a combination of CAD and hypertension (72 (81.8%) vs. 79 (59.4%), p < 0.001). In addition, acute/chronic kidney diseases (18 (20.5%) vs. 13 (9.8%), p = 0.022) and cancer were more common (12 (13.6%) vs. 8 (6.0%)), p = 0.046).Among the acute complications that occurred during the stay of patients in the ICU, the deceased patients experienced significantly higher rates of the following conditions: stroke (10 (11.4%) vs. 3 (2.3%), p = 0.006), acute heart failure (9 (10.2%) vs. 4 (3.0%), p = 0.038), pulmonary embolism (9 (10.2%) vs. 3 (2.3%), p = 0.014), infectious toxic shock (10 (11.4%) vs. 1 (0.8%), p = 0.001), acute respiratory distress syndrome (78 (88.6%) vs. 6 (4.5%), p < 0.0001), endstage of renal failure (62 (80.5%) vs. 82 (62.1%), p = 0.006). Additionally, among rhythm disturbances, atrial fibrillation was more prevalent in deceased patients and was associated with a lower survival rate (31 (35.2%) vs. 19 (14.3%), p = 0.0001).Conclusions. The study demonstrated that clinical factors associated with mortality in patients with a severe course of COVID-19 include patient age and с omorbidity such as hypertension, CAD, heart failure and rhythm disorders. Tachyarrhythmias and bradyarrhythmias were more often observed in deceased patients, in particular, they had more frequent AF, which emphasizes its role as a predictor of poor prognosis in patients with COVID-19.